SAT0011 Characteristics, Needs and Sources of Information of A French Online Community of Systemic Lupus Erythematosus Patients. (10th June 2014) - Meunier, B.; Harle, J.-R.; Chekroun, M.; Chiche, L.
Abstract : Background: There is a lack of data about needs and sources of information of patients living with rare diseases. Internet forums are understudied resources to know more about people living with such diseases. Carenity is the first French online platform allowing peer-to-peer exchanges, within online communities dedicated to specific diseases, including Systemic Lupus Erythematosus (SLE). Objectives: Describe characteristics of the Carenity SLE community and identify needs and sources of information of SLE patients. Methods: One year after creation of the SLE community, all the posts of the forum dedicated to LSE were analyzed. A focused cross-sectional online survey was also proposed to members of the community. Results: The SLE community included 521 people (female: 93%; mean age: 38.9 years) geographically distributed homogeneously throughout territory. From a total of 6702 posts, 2232 could be classified into specific topics. The 10 most popular topics (836 posts) were "Lupus and [...]": treatment (220), fatigue (112), entourage (106), sun exposure (97), diagnosis (58), autoimmune diseases (55), pregnancy (55), contraception (49), symptoms (49) and sexuality (35). Additional topics of interest (with at least 10 posts each) were "Lupus and [...]": nutrition, physical activity, work, weight, psychological impact, toxics, vaccines, fibromyalgia, global management, outcomes and paraclinical investigations. From April to May 2013, 112 patients fulfilled the online survey. Only 17 (15%) patients had already heard about lupus when diagnosed. They reported, according to evolution of the disease, lack of information about: 1) At diagnosis: outcome, treatments, daily life, patient associations, symptoms, disease, psychosocial aspects; 2) At treatment initiation: side effects, long-term effects, duration/cessation, type, mechanism of action. Sources of information were various with relative variations according to timing respectively "just before", "just after diagnosis" and "before treatment initiation": healthcare providers (51/61/67%), journals/magazines (7/12/6%), patient associations (11/23/9%), lupus websites (51/77/40%), web forums/blogs (34/53/19%). All responders except one said they used Internet to look for information about LES: via search engines (74%), health portals (55%), forums (46%), patients' associations' websites (46%), French patients blogs (31%), Facebook (21%). Online services they said to be interested in were: ongoing trials (46%), platforms to ask questions to healthcare providers (43%) and non healthcare providers such as jurists (21%), medical information about SLE (41%), therapeutic education programs (33%), advices about administrative measures (32%), advices about treatment management (29%), measurement and monitoring of treatment tools (21%), self notification of side effects (16%). Conclusions: This study provides original data on the needs and sources of information of SLE patients, especially via Internet medias. This could be used to improve content and form and provide more relevant information. Disclosure of Interest: B. meunier: None declared, J.-R. harle: None declared, M. chekroun Shareholder of: carenity funder, L. Chiche: None declared DOI: 10.1136/annrheumdis-2014-eular.2398